2016
DOI: 10.15179/ces.18.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Cost Accounting as a Possible Solution for Financial Sustainability of Croatian Public Hospitals

Abstract: The purpose of this paper is to present the current usage of cost accounting methodology in Croatian public hospitals through conducted empirical research and to provide opinions of accountants and financial officers regarding possible implementation of cost accounting methodology in public hospitals.In the paper, the authors analyze the accounting system in Croatian public hospitals, identifying the flaws of the current accounting system with regard to the recording and allocation of costs. National healthcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…Limitations of information technologies (IT). Lack of technical support as an obstacle to implementing an accounting system is notable, especially the lack of an IT system (Bruno and Lapsley, 2018; Gigli et al , 2018; Hladika, 2022; Jorge et al , 2019; Lutilsky et al , 2016; Scheers et al , 2006; Venieris and Cohen, 2004) in both developed and developing countries. For instance, Caruana (2017) found that there was an insufficient allocation of funds for the acquisition of the new IT system, resulting in a strong barrier to the implementation of the accounting reform in Malta.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Limitations of information technologies (IT). Lack of technical support as an obstacle to implementing an accounting system is notable, especially the lack of an IT system (Bruno and Lapsley, 2018; Gigli et al , 2018; Hladika, 2022; Jorge et al , 2019; Lutilsky et al , 2016; Scheers et al , 2006; Venieris and Cohen, 2004) in both developed and developing countries. For instance, Caruana (2017) found that there was an insufficient allocation of funds for the acquisition of the new IT system, resulting in a strong barrier to the implementation of the accounting reform in Malta.…”
Section: Resultsmentioning
confidence: 99%
“…The adoption of new accounting standards requires resources such as investments in IT systems. Lutilsky et al (2016) identified that the greatest constraint to the implementation of the accrual accounting basis is political support and IT support. Scheers et al (2006) sought to determine whether the information technology system has caused problems in Australia and the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Since operationalisation of the NPM concept started much later in the CEE than in Western European countries, the developing countries and CEEC are much less represented (Duhovnik, 2007;Hassan, 2005;Naranjo-Gil, 2004;van Helden & Uddin, 2016) in the literature, especially Slovenia and Croatia (Albreht et al, 2009;Dimitri c, Skalamera-Alilovi c, & Duhovnik, 2016;Farka s, 2017;Lutilsky, Zmuk, & Dragija, 2016;Va si cek et al, 2016). There is a limited scope of the literature focusing mainly on MASs and its characteristics in relation to RBV, although the research of MAS, is more frequent and systematic.…”
Section: Legitimation View Contra Instrumental Viewmentioning
confidence: 99%
“…Konsep ini mengakui pentingnya kesalingterhubungan manusia dengan yang lainnya, tidak sebatas pada hubungan antarmanusia, tetapi juga dengan semua hal yang hidup, termasuk dengan tanah (Lutilsky, Žmuk, & Dragija, 2016;Velte & Stawinoga, 2017). ANTAM mengakui adanya hubu ngan dengan alam sekitar dan tanah "ANTAM menyadari bahwa setiap daerah operasi memiliki keunikan, kebutuhan, dan aset sosial, ekonomi, dan budaya yang berbeda-beda sehingga memerlukan pendekatan serta program CSR yang berbeda" (PT ANTAM, 2015:74).…”
Section: Metodeunclassified